Estimating Yield Gaps With Limited Data: An Application to United States Wheat. (20th January 2015) - Tack, Jesse; Barkley, Andrew; Lanier Nalley, Lawton
Abstract : The objective of this research is to estimate and analyze the gap between in‐trial yield potential, on‐farm yield potential, and actual on‐farm wheat yields. Yield gaps are quantified by measuring how varietal mean yields have changed over time, due to productivity increases generated by public and private wheat breeding programs. Variety performance trial data for Kansas winter wheat are used to summarize the evolution of wheat yields over the time period 1985 to 2011. A measure of yield potential is compared to actual on‐farm yields to derive implications for wheat industry stakeholders. Persistent and expanding yield gaps between potential yield and actual on‐farm yield are measured and analyzed. Producers' variety adoption decisions explain a relatively small portion of this gap, and producers have become more effective at identifying and adopting yield‐enhancing varieties over time. The largest portion of these gaps was explained by on‐farm production decisions.